In the crossroads of the urban territoriality (2006)
The author proposes a new action field for planning and, in general, for all the sciences related to urban phenomenon. It refers to a different perspective on territory, were territoriality is understand as the place capability to influence social behavior, to say, a perspective able to value those aspects –conditions and potentials of territorial resources– that have a positive effect on development and rehabilitation processes.